Assessing the nature of soil acidity in per-humid, Sub-tropical Meghalaya in North Eastern region of India - ROY, PARTHA DEB; JENA, R.K.; RAY, P.; SHARMA, R.P.; BANDYOPADHYAY, S.; RAMACHANDRAN, S.; MITRAN, T.; SAHA, B.N.; SINGH, S.K.; RAY, S.K. (Journal of Soil and Water Conservation, 2022)
Soils of Meghalaya in the north eastern region of India were characteristically acidic in nature. The present work was undertaken to assess the spatial variability of soil acidity as well as to study different forms of soil acidity across various landscape positions and land uses and their relationship with soil properties. Soil samples were collected from surface (0-15cm) in 509 locations throughout the study area and also from depth wise viz., 0-15, 15-30, 30-45 and 45-60 cm in four distinct landscape positions viz. plateau top, side slope, foot slope and valley in the Umsning block of Ri-bhoi district, Meghalaya. Surface soils of majority of the study area (77%) came under very strongly acidic (pH 4.5 – 5.0) category. Total potential acidity (TPA) as well as exchangeable acidity (EA) was much higher in elevated positions as compared to the valley. A decreasing trend of EA with soil depth was observed in all the soils. Higher amount of exchangeable aluminium (0.09 to 2.95 cmol(p+)kg-1) was measured in most of the landscape positions except in valleys. The study indicated that neutralizing high amount of EA in elevated landscapes along with acid tolerant crops or cultivar could be a suitable strategy to address these acid soils.